2018
DOI: 10.1016/j.dental.2018.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Triethylene glycol dimethacrylate impairs bioenergetic functions and induces oxidative stress in mitochondria via inhibiting respiratory Complex I

Abstract: TEGDMA inhibits CI in the respiratory chain, which explains effects induced by TEGDMA on redox homeostasis, apoptotic and necrotic cell deaths described in previous studies. Identification of the molecular target of TEGDMA may influence the development of relevant biomaterials and may induce new therapeutic strategies to control the adverse effects of resin monomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 90 publications
3
8
1
3
Order By: Relevance
“…Studies on permeabilized DPSC affirmed our earlier observation, that oxidation of CI substrates (a-KG, pyruvate plus malate and glutamate plus malate) is sensitive to TEGDMA-mediated inhibition ( Figure 2 B–D). Contrary to that the results obtained in isolated mitochondria [ 48 ], in succinate supported permeabilized cells a small but statistically significant inhibition of oxygen consumption was observed ( Figure 2 A). A possible explanation of this controversy could be the incomplete permeabilization of the cell membrane and the consequent imperfect wash out of CI substrates which could “contaminate” the oxidation of succinate via their high sensitivity to TEGDMA-mediated inhibition.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Studies on permeabilized DPSC affirmed our earlier observation, that oxidation of CI substrates (a-KG, pyruvate plus malate and glutamate plus malate) is sensitive to TEGDMA-mediated inhibition ( Figure 2 B–D). Contrary to that the results obtained in isolated mitochondria [ 48 ], in succinate supported permeabilized cells a small but statistically significant inhibition of oxygen consumption was observed ( Figure 2 A). A possible explanation of this controversy could be the incomplete permeabilization of the cell membrane and the consequent imperfect wash out of CI substrates which could “contaminate” the oxidation of succinate via their high sensitivity to TEGDMA-mediated inhibition.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been observed that TEGDMA inhibits mitochondrial O 2 consumption at the CI level [48]. In line with that study, our present results confirm the mitochondrial targets of TEGDMA, mainly the vulnerability of CI.…”
Section: Effects Of Tegdma and Mb On Bioenergetics Of Isolated Mitochsupporting
confidence: 93%
See 3 more Smart Citations